Adsorption and Catalytic Oxidation of Methane by Indium Oxide Sensors Doped with Platinum - V.V. Golovanov; B.V. Nazarchuk; V.V. Golovanova (Журнал нано- та електронної фізики)
Differential scanning calorimetry and X-ray photoelectron spectroscopy were used to investigate the mechanism of methane interaction with platinum-doped indium oxide surface. It was shown that sorption processes have a significant impact on the sensor response at the operating temperatures below 370 С for doped Pt/In2O3 and below 500 С for In2O3-based sensors. Above the critical temperatures the sensor response is dominated by the catalytic oxidation of methane. The operating temperature of sensors was decreased on 80 С by doping of the material with Pt 0.5 wt.%. Thus formed PtxIny clusters have a significant effect on the In¬2O3 catalytic properties. The developed sensors demonstrated high sensitivity, small operating parameters range, and low consuming power together with simple production technology.